Pomacea insularus (Gastropoda : Pilidae) : its control under the integrated pest management (IPM) concept - Suryanto, Edi (2000)
Three control measures of Pomace a insularus as parts of IPM (Integrated Pest Management) components were studied; firstly the development of plant molluscicides, secondly the use of fish as its biological control and thirdly its utilisation as quail (Coturnix coturnix japonica) feed. Leaf powder of yellow flame (Peltophorum pterocarpum) was found to be quite effective in killing the snails. The powder is water soluble (28% solubility) and yielded high extracts (25% of water extraction and 23% of methanol extraction). The LC₅₀ value of this powder solution is about 91 mg/L at 72 h. exposure, on two-week-old test snails. Saponins were the active compounds found in the yellow flame leaves. Kept in solution form, the molluscicide strength deteriorated after 30 days with toxicity level reduced to 34%. The toxicity of the molluscicide in the field trials was found to be twice lower than that of Tea Seed Cake (TSC) powder, a molluscicide used in Malaysia. The broadcasting application of 150 kg/ha of this leaf powder molluscicide in 15 cm deep rice field (equivalent to 100 mg/L) killed 100% of the adult snails in three days as compared to about 75 kg/ha (equivalent to 50 mg/L) of TSC. Study on the control of the snails using fishes revealed that black carp, Mylopharyngodon piceus and hybrid African catfish, Clarias sp. were good snail predators. In the laboratory trials the former was more vigorous, consuming at the rate of 60% of its body weight, within 24 h, while the latter consumed only 7%. Due to the shape and size of its mouth, black carps had greater ability in swallowing the snails than catfish. Young black .carp of 25 g in size could consume snails of up to about 1.0 em in shell length. There were high correlationships between the size of snails consumed and the size of fish and the mouth width, with the equation ofY = 0.26 Ln (X) + 0.16 ( r2 = 0.93) and of Y = 0. 4 Ln (X) + 1.25 (r2 = 0.93), respectively. Adult catfish (119 - 171 g) could only consume snails of up to 1.5 em shell length. Results from the release of catfish into the rice field showed a clear trend of a reduction in the snail population. Macroinvertebrates populations presence in the rice field were another source of food supply to the fish, thus enabling the fish to grow without being given supplementary food. Biological control of this snail using fish was, however, confronted with the problem of predators such as birds, crab, eel and otters. Snail meal contained high protein (32%) and mineral (26%). It could be a substitute for fish meal, meat and bone meal or soya bean meal as quail feed without having any effect on its growth performance. Birds fed with snail meal also performed as good as those given commercial feed. The performance indices such as average daily gain (ADG), feed conversion ratio (FeR) and carcass percentage of birds given snail meal protein was comparable with those given conventional protein source. A palatability test conducted had shown that meat of the bird fed with snail meal was well accepted by food panelists. Each control measure of snails that has been studied demonstrated promising results. Thus the implementation of the control measures could be exercised in the field integrally to achieve managable control of the population of Pomace a insularus